2008
DOI: 10.1051/0004-6361:200810889
|View full text |Cite
|
Sign up to set email alerts
|

Rotational spectrum of deuterated and $\mathsf{^{15}}$N ethyl cyanides: CH3CHDCN and CH2DCH2CN and of CH3CH2C$\mathsf{^{15}}$N

Abstract: Context. Ethyl cyanide is an abundant molecule in hot molecular clouds. Its rotational spectrum is very dense and several hundreds of rotational transitions within the ground state have been identified in molecular clouds in the 40−900 GHz frequency range. Lines from 13 C isotopically substituted ethyl cyanide were identified in Orion. Aims. To enable the search and the possible detection of other isotopologues of ethyl cyanide in interstellar objects, we have studied the rotational spectrum of deuterated ethy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…In 2007 we began a close collaboration between astronomers and spectroscopists to reduce the uncertainty due to unidentified lines in spectral surveys. New isotopologues of ethyl cyanide and methyl formate (Demyk et al 2007;Margulès et al 2009Margulès et al , 2010Carvajal et al 2009;Coudert et al 2013) and new vibrationally excited states of formamide (Motiyenko et al 2012), ethyl cyanide , and vinyl cyanide (López et al 2014) have been studied in spectroscopy laboratories and detected in Orion KL for the first time space. Altogether, we reduced 3000 of unidentified lines through these studies.…”
Section: Resultsmentioning
confidence: 99%
“…In 2007 we began a close collaboration between astronomers and spectroscopists to reduce the uncertainty due to unidentified lines in spectral surveys. New isotopologues of ethyl cyanide and methyl formate (Demyk et al 2007;Margulès et al 2009Margulès et al , 2010Carvajal et al 2009;Coudert et al 2013) and new vibrationally excited states of formamide (Motiyenko et al 2012), ethyl cyanide , and vinyl cyanide (López et al 2014) have been studied in spectroscopy laboratories and detected in Orion KL for the first time space. Altogether, we reduced 3000 of unidentified lines through these studies.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C isotopomers of ethyl cyanide were detected first in Orion IRc2 (Demyk et al 2007) and soon thereafter in Sgr B2(N) (Müller et al 2008). Margulès et al (2009) reported the detection of C 2 H 5 C 15 N in Orion IRc2.…”
Section: Introductionmentioning
confidence: 91%
“…As an example of the scope of this line survey in the field of molecular spectroscopy, Demyk et al (2007), Margulès et al (2009), Carvajal et al (2009), and Margulès et al (2010 identified more than 600, 100, 600, and 100 lines from the 13 C and 15 N isotopologues of CH 3 CH 2 CN, the 13 C isotopologues of HCOOCH 3 , and CH 3 OCOD, respectively. Many of the remaining U-lines are certainly due to isotopologues of other abundant species.…”
Section: The Line Surveymentioning
confidence: 99%